Functional Analysis of Aquaporin Water Permeability Using an Escherichia coli-Based Cell-Free Protein Synthesis System - Yue, Ke; Jiang, Jihong; Zhang, Peng; Kai, Lei (Frontiers in Bioengineering and Biotechnology, 2020)
Aquaporins are essential water channel proteins found in all kingdoms of life. Although the water permeability of aquaporins has been well characterized, sample preparation for aquaporin water permeability assays remains challenging and time-consuming. Besides the difficulty in overexpressing membrane proteins in a cell-based expression system, the unique requirement for homogeneity in aquaporin proteoliposome sample preparations for water transport assays further increases the complexity. In this study, a complementary Cell-free Protein Synthesis (CFPS) method is described in detail, providing three different strategies for the preparation of aquaporin proteoliposome samples. Aquaporin can be produced either as a pellet fraction and then resolubilized, or co-translationally as a detergent-soluble fraction. Furthermore, aquaporin can be directly incorporated into liposomes, which was included in the CFPS reactions. Although proteoliposomes tend to fuse during the incubation of the CFPS reactions, an additional treatment of the fused samples with detergent, followed by a detergent removal step, can re-form homogenously sized proteoliposomes suitable for functional analysis. Using this method, we successfully characterized aquaporins from both prokaryotic and eukaryotic organisms. In particular, in the presence of liposomes, the developed CFPS expression system is a fast and convenient method for sample preparation for the functional analysis of aquaporins.